EM BUSCA DO ETHOS CONSTITUCIONAL BRASILEIRO: UM ESTUDO COMPARADO DO CONSTITUCIONALISMO LIBERAL - Muniz da Conceição, Lucas Henrique (Constituição, Economia e Desenvolvimento: Revista Eletrônica da Academia Brasileira de Direito Constitucional, 2020)
This article argues that the Brazilian constitutional ethos is constructed upon an asymmetrical distribution of powers which, if not addressed, imposes a hindrance to the protection of democracy and the human rights recognised in the constitutional pact. The establishment of the 1988’s Constitution in Brazil represented a strong political stance in which the country sought to overcome its democratic deficiencies and human rights violation practices after experiencing an intense military dictatorship. Thus, the constituent assembly was strongly influenced by the liberal perspective of constitutionalism, establishing a system that defined constitutional rights and principles, recognizing their normative force within the legal framework of the state. On the other hand, liberal constitutionalism tends to suppress the political nature of the constitution. How this development impacts the exercise of power in Brazil and the United States? This article proposes to analyse critically how the configuration of the strictly liberal perspective of constitutionalism impacts Brazilian socio-political structure, considering both the tendency of liberal constitutionalism to overshadow the political aspect of the constitution and the specificities of Brazilian distribution of power within the state.